Exploring Honai construction as a resource for mathematics learning - Kho, Ronaldo; Tandililing, Pitriana; Yektiningtyas, Wigaty (Journal of Honai Math, 2025)
Cultural heritage plays a critical role in providing context for mathematical learning, offering opportunities to enhance both academic understanding and cultural appreciation. However, there is a gap in integrating ethnomathematical knowledge into formal education, particularly in connecting local cultural practices with abstract mathematical concepts. This study addresses this gap by examining the ethnomathematics of the Dani community, focusing on the construction of the Honai, a traditional structure that reflects the community's indigenous knowledge and craftsmanship. The research aims to identify and analyze the mathematical concepts embedded in the Honai's construction, thereby demonstrating how these principles can inform culturally responsive mathematics education. Using a qualitative ethnographic methodology, data were collected through participant observation, in-depth interviews with traditional builders and community elders, and document analysis. The findings reveal that the Honai incorporates various mathematical principles, including circular geometry in its base, conical or paraboloid shapes in its roof, and non-standard measurement techniques based on body spans and visual alignment. These results highlight the rich geometric, proportional, and spatial reasoning inherent in the Honai's design and construction. The study demonstrates that incorporating the Honai's construction principles into mathematics instruction can enhance student engagement and deepen conceptual understanding by linking abstract concepts to culturally significant practices. This culturally responsive approach not only bridges traditional knowledge with academic content but also fosters pride in cultural identity. By leveraging cultural artifacts like the Honai, this research contributes to the development of inclusive and effective educational strategies that enrich mathematics teaching and learning.